The importance of the soluble and colloidal pools for trace metal cycling in deep-sea pore waters - Paul, Sophie A. L.; Schmidt, Katja; Achterberg, Eric P.; Koschinsky, Andrea (Frontiers in Marine Science, 2024)
Physical and chemical trace metal speciation are important for our understanding of metal cycling and potential toxicity to marine life. Trace metals can behave differently in diffusion processes or particle-solution interactions and have different bioavailabilities depending on their physical and chemical forms, which often depend on redox conditions. Here we investigated dissolved (< 0.2 µm) and soluble (< 0.02 µm) concentrations of Mn, Co, Ni, Fe, Cu, V, Mo, U, Cd, and As in oxic and suboxic deep-sea sediments of the central equatorial Pacific Ocean. Vanadium, Mo, U, As, and Cd showed no significant concentration differences between their dissolved and soluble forms, suggesting that they are present as inorganic ionic species or organic complexes in the truly dissolved or small colloidal fraction. In contrast, the colloidal fraction (> 0.02 µm < 0.2 µm) of Mn, Co, Ni, and Cu increased with depth in oxic pore waters and Fe had the largest but variable colloidal pool. Soluble Mn, Co, and Ni were released in the uppermost 2-4 cm in the sediment because of reductive dissolution. The increasing colloidal fraction with depth suggests a decrease in the concentration of small organic ligands with depth, that are abundant in the surface sediment pore waters, and instead an increasing importance of larger (> 0.02 µm) inorganic nanoparticles and colloids such as Mn and Fe (oxyhydr)oxides that control Mn, Fe, and Co cycling at depths > 10 cm. The distribution of Ni and Cu cannot be exclusively explained by inorganic nanoparticles and a shift from low to larger high molecular weight organic ligands might occur. These findings provide new insights into trace metal distributions in the dissolved phase, highlighting the diversity of metal complexes and the need to incorporate these in future calculations of benthic metal fluxes and ecotoxicity assessments, especially in oxic pore waters.